Research on Intelligent Networking Architecture for the Integrated Space-Terrestrial Networks - Tingting ZHANG; Nan WU; Haipeng YAO (天地一体化信息网络)
The integrated space-terrestrial networks (ISTN), characterized by the high-dynamic of topology, the diversifi cation of services and the constrained resource of satellites, face great challenges in the integration of networking.To achieve network capabilities of intelligent reconstruction, on-demand adjustment, eff ective management and control, the intelligent networking method for ISTN by applying SDN, NFV and artifi cial intelligence were studied.In-depth analysis of the development status of the world-earth fusion network, an intelligent and virtualization-driven world-earth fusion network architecture was proposed.On this basis, to addressed the challenges of intelligent networking brought about by network element heterogeneity, large space-time scale, and diff erentiated service requirements, the multidimensional heterogeneous data plane resource pooling, multi-domain collaborative sensing function on-demand deployment, multi-layer multi-domain hybrid network autonomous control, centralized and distributed network intelligence for ＆quot;cloud-edge＆quot; collaboration, etc.were proposed, which realized on-demand reconstruction of the world-earth fusion network and intelligent service guarantee capabilities.